Review—Textile Based Chemical and Physical Sensors for Healthcare Monitoring. Issue 3 (21st January 2020) - Hatamie, Amir; Angizi, Shayan; Kumar, Saurabh; Pandey, Chandra Mouli; Simchi, Abdolreza; Willander, Magnus; Malhotra, Bansi D.
Abstract : The emergence of textile-based wearable sensors as light-weight portable devices to monitor desired parameters, has recently gained much interest and has led to the development of flexible electronics on non-rigid substrates. The flexible biosensors may result in improved sports performance, to monitor the desired bodies for injuries, improved clinical diagnostics and monitor biological molecules and ions in biological fluids such as saliva, sweat. In addition, they could help users with different types of disorders such as blindness. In this context, new composite and nanomaterials have been found to be promising candidates to obtain improved performance of the textile based wearable devices and to optimize the structures for intimate contact with the skin for better functionality. This review aims to provide the most recent cutting-edge information on emergence, fabrication, materials, and applications of chemical and physical flexible and stretchable textile-based (bio)sensors. Besides this, we discusss the recent key innovations and applications of textile-based sensors in healthcare.